Significance of plasma hepatocyte growth factor in diagnosis of benign and malignant solitary pulmonary nodules - Yu, Haixin (Int J Clin Exp Pathol, 2015)
Purpose: We aimed to figure out the difference of serum hepatocyte growth factor (S-HGF) level between benign and malignant solitary pulmonary nodules (SPNs) patients. Methods: The study comprised 42 serum samples from SPNs patients and 10 serum samples of healthy donors. The HGF level was measured by the commercially enzyme-linked immunosorbent assay (ELISA) kit. Results: By statistical analysis, the S-HGF levels of the malignant SPNs patients were significantly higher than that of control group (P < 0.05). Moreover, the levels of S-HGF in malignant group were also significantly higher than that in benign group (P < 0.05), while there was no significant difference between the benign and control group (P > 0.05). The levels of S-HGF were also shown no statistically significant difference (P > 0.05) in different pathologic types of lung cancer patients. In addition, the incidence of malignant SPNs increased when the S-HGF level ≥ 250 pg/ml. Conclusion: The detection of S-HGF level may be a new detection method used for the rapid diagnosis of benign and malignant SPNs.